Knowledge, Attitudes, and Practices of Complementary Feeding among Mothers at the Stunting Locus Area: A Cross-Sectional Study in West Sulawesi - Nurbaya Nurbaya; Afifah Bidayah; Zaki Irwan; Yudianti Yudianti (Poltekkes Kemenkes Palu, 2023)
Introduction: Bebanga Village, Kalukku District recorded a stunting prevalence of 38.5%. Stunting is caused by various factors, including mothers' lack of knowledge about IYCF. Purpose: To find out the description of knowledge, attitudes, and complementary feeding practices in mothers and the nutritional status of children in the stunting locus area. Methods: The study used a cross-sectional design conducted from January to May 2023 at the Stunting Locus in Bebanga Village, West Sulawesi. A total sample of 148 was calculated using proportional random sampling. Measuring the nutritional status of children uses four indicators: weight/age, height/age, weight/height, and BMI/age Results: The prevalence of stunting children in was 48.0%. As many as 51.5% of mothers had sufficient knowledge about complementary feeding, 51.4% of mothers had a negative attitude about complementary feeding, and as many as 76.4% of mothers practiced complementary feeding not according to standards. The chi-square test showed that the aspects of knowledge (p-value=0.165), attitude (p-value=0.880), and practice (p-value=0.280) of complementary feeding among mothers were not related to the incidence of stunting among children at the stunting locus area. Conclusion: Many stunted children were found among mothers with good knowledge and attitudes toward ICYF but lacked practice.